A systematic review of the effect of running shoes on running economy, performance and biomechanics: analysis by brand and model - Ruiz-Alias, S. A.; Molina-Molina, A.; Soto-Hermoso, V. M.; García-Pinillos, F. (Sports Biomechanics, 2023)
This systematic review aims to synthesise the effects of current shoe models in each shoe category and their specific features on running economy, performance and biomechanics. Electronic databases such as Web of Science, SPORTDiscuss, PubMed and Scopus were used to identify studies from 2015 to date. Due to the existing lack of consensus to define running shoes, only studies that specified the shoe brand and models used to assess their effect over runners with a certain level of fitness and training routine were included. Quality assessment of cross-sectional and intervention studies was conducted by three independent raters using a modified version of the Quality Index and the PEDro scale, respectively. A total of 36 articles were finally included, involving the analysis of 61 different shoe models over 10 different topics (i.e., running economy, running performance, spatiotemporal parameters, ground reaction forces, joint stiffness, achilles tendon, plantar pressure, tibiofemoral load, foot strike pattern and joint coordination). With this review, runners and practitioners in the field that are concerned about selecting a suitable shoe for performance, training, or injury prevention functionality have clear information about the effects of the current shoe models and their specific features.